The effectiveness of a training program in developing the cognitive skills of using virtual schools for teaching among education teachers in Jazan region - Hamdhy, Nawal Hussain Ahmad (Journal of Educational and Psychological Sciences, 2021)
The aim of the study is to measure the effectiveness of a training program in developing the cognitive skills of using virtual schools for teaching among education teachers in Jazan region. To achieve the study objectives, the researcher prepared a training program that involves a cognitive skills test for using virtual schools in teaching. Through the use of descriptive, analytical and quasi-experimental approaches that are one-group design, and the pre and post application on a sample that was represented by (30) teachers whom were selected randomly from many schools in Jazan region, in the governorate of Ahad al Masarihah, , the study found out that there are differences that are statistically significant at the significance level (α ≤ 0.05) between the mean scores of the teachers (study sample) in the pre and post application of the cognitive skills test of the use of virtual schools in teaching in the favor of the post application. The results of the study concluded that the modified gain coefficient Black increased more than (1.2) compared to the pre and post application of the training program in the favor of the post application and reached the maximum level which indicates the effectiveness of the training program in developing the cognitive skills of using virtual schools for teaching by education teachers in Jazan region (study sample). And in light of the study findings, a set of recommendations were presented, including: benefitting from the training program that was prepared by the researcher, that is in order to develop the cognitive skills for the use of virtual schools in teaching by education teachers at all different educational levels, and the necessity of approving it by competent educational institutions and generalizing it to training departments in Jazan region and the other regions in the Kingdom of Saudi Arabia.